2017
DOI: 10.1038/s41598-017-03115-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Brazilian green propolis that contains flavonols against mutant copper-zinc superoxide dismutase-mediated toxicity

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by the selective and progressive loss of motor neurons. The purpose of this study was to clarify effects of brazilian green propolis and the active ingredient against ALS-associated mutant copper-zinc superoxide dismutase (SOD1)-mediated toxicity. Ethanol extract of brazilian green propolis (EBGP) protected N2a cells against mutant SOD1-induced neurotoxicity and reduced aggregated mutant SOD1 by induction of autophagy. Kaemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 37 publications
(62 reference statements)
4
60
0
Order By: Relevance
“…Hence, the geometrical properties of protein upon binding the ligands suggested that kaempferol could be a better promising therapeutic drug candidate than kaempferide, which could hinder the formation of aggregates in mutant SOD1. Moreover, our results corroborated with the reports from the experimental studies asserting that kaempferol has greater ability in impeding the formation of aggregates in mutant SOD1 [25].…”
Section: Impact Of Kaempferol and Kaempferide On The Secondary Structsupporting
confidence: 91%
See 2 more Smart Citations
“…Hence, the geometrical properties of protein upon binding the ligands suggested that kaempferol could be a better promising therapeutic drug candidate than kaempferide, which could hinder the formation of aggregates in mutant SOD1. Moreover, our results corroborated with the reports from the experimental studies asserting that kaempferol has greater ability in impeding the formation of aggregates in mutant SOD1 [25].…”
Section: Impact Of Kaempferol and Kaempferide On The Secondary Structsupporting
confidence: 91%
“…Numerous biological and pharmacological properties, such as antibacterial, anti-inflammatory, and antioxidative activity are reported with propolis [27,28]. Two polyphenols derived from propolis, kaempferol, and kaempferide are its major effective components, which are known to have neuroprotective properties against mutant SOD1 protein as reported from the recent experimental studies [25].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the detailed chemical composition of various types of propolis differ, based on geographical origin, in general, typical raw propolis contains 50% resins and vegetable balsams, 30% waxes, 10% essential and aromatic oil, 5% pollen, and 5% other bioactive compounds (Popova, Reyes, Le Conte, & Bankova, ). This product has been extensively used in foods, beverages, and nutritional supplements, because of bioactive constituents such as phenolic compounds, flavonoids, terpenes, beta‐steroids, and aromatic acids (Popova et al, ; T. Ueda et al, ). The health‐promoting properties of propolis have been investigated in various animal studies (Seven, Yilmaz, Seven, & Kelestemur, ; Yildirim et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, more than 180 types of SOD1 pathogenic mutations have been identi ed in ALS patients [33]. Among those, the pathogenic SOD1 G85R mutation has been most frequently studied [34,35,36,37].…”
Section: Introductionmentioning
confidence: 99%